Modeling an optical diaphragm for human pulse pressure detection - Hasikin, K.; Soin, N.; Ibrahim, F. (2009)
This paper presents the modeling of an optical diaphragm behavior for human pulse pressure detection. In this study, the comparison between the performance of the polyimide and silicon nitride diaphragm has be analyzed. The effect of diaphragm's radius and thickness on static and frequency response are also investigated. The findings show that the polyimide diaphragm is more sensitive than the silicon nitride diaphragm. The radius of the polyimide diaphragm has more effect on the deflection, sensitivity, and resonance frequency as compared to the diaphragm's thickness. It can be concluded that the polyimide diaphragm achieves the optimum performance in term of the deflection, sensitivity, and resonant frequency for human pulse pressure detection.